1990
DOI: 10.1177/089198879000300208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Normal Serum Vitamin B12 and Folate Levels to Cognitive Test Performance in Subtypes of Geriatric Major Depression

Abstract: This retrospective study evaluated the relationships between normal serum vitamin B12 and folate levels and neuropsychologic measures in a sample of 60 geriatric inpatients with psychotic depression, nonpsychotic depression, bipolar disorder, and dementia--all consecutively referred for cognitive testing. The psychotic depression subgroup demonstrated numerous significant positive correlations between B12 and cognitive subtests not seen in other diagnostic subgroups, especially those of IQ, and verbal and visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The median years of education was 15 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Twenty-five (75.8%) patients were lacto-vegetarian, seven (21.2%) were infrequent nonvegetarian (less than two times per month), and only one (3.0%) consumed non-vegetarian food more than two times per month.…”
Section: Subjects' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median years of education was 15 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Twenty-five (75.8%) patients were lacto-vegetarian, seven (21.2%) were infrequent nonvegetarian (less than two times per month), and only one (3.0%) consumed non-vegetarian food more than two times per month.…”
Section: Subjects' Characteristicsmentioning
confidence: 99%
“…Improvement following vitamin B12 therapy has been demonstrated in the patients presenting with cognitive or behavioral abnormalities in comparison with the controls on verbal fluency test, but other investigators have failed to confirm these optimistic results. 10,11 Some authors feel that vitamin B12 treatment may improve frontal lobe and language functions in patients with cognitive impairment but rarely reverses dementia. 12 P3 has been used to document cognitive dysfunction especially to monitor the effect of therapy in Alzheimer's disease, HIV-associated dementia, and encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a number of published studies which have suggested links with vitamin status and cognitive performance amongst the elderly (for example, see Goodwin et al 1983;Sommer & Wolkowitz, 1988;Bell et al 1990;Riggs et al 1996), these studies have been correlational in nature and have provided no clear hypothesis as to the mechanisms underlying these relationships. One intervention study, however, revealed no effect of supplementation on cognitive performance (Chome et al 1986), although this can possibly be interpreted in terms of the low subject numbers and the relatively short period of supplementation (5 weeks).…”
Section: B-complex Vitamins Folate and Neural Functionmentioning
confidence: 99%
“…Bell et af. [21] reported an association between low or low-normal concentration of serum cobalamin and blood folate and certain neuropsychiatric disorders in elderly subjects, particularly depression. Therefore in this study we determined plasma homocysteine and its main determinants [22], serum cobalamins, blood folate, and serum creatinine in 741 psychogeriatric patients and compared the findings with those in a reference population (n = 163).…”
Section: Introductionmentioning
confidence: 99%